А)х-3/х+2=6 б)х-5/х-3=х/х+1 ПОМОГИТЕ!
1) x-3=6x+12 -5x=12+3 -5x=15 x=-3 2) (x-5)(x+1)=x(x-3) x^2-4x-5=x^2-3x x^2-x^2-4x+3x=5 -x=5 x=-5
А) x- \frac{3}{x}-4=0 => \frac{ x^{2} -4x-3}{x} =0 =>" alt="x- \frac{3}{x} +2=6 => x- \frac{3}{x}-4=0 => \frac{ x^{2} -4x-3}{x} =0 =>" align="absmiddle" class="latex-formula"> D=16+4*3=28 => " alt="\left \{ {{x^{2} -4x-3=0} \atop {x \neq 0}} \right.=> D=16+4*3=28 => " align="absmiddle" class="latex-formula"> x_{1} =2+ \sqrt{7} , x_{2}=2- \sqrt{7}" alt="D=16+4*3=28 => x_{1} =2+ \sqrt{7} , x_{2}=2- \sqrt{7}" align="absmiddle" class="latex-formula"> б) x- \frac{5}{x}=2 => \frac{ x^{2} -2x-5}{ x^{2} }=0 => " alt="x- \frac{5}{x} = \frac{x}{x} +1=> x- \frac{5}{x}=2 => \frac{ x^{2} -2x-5}{ x^{2} }=0 => " align="absmiddle" class="latex-formula"> " alt="\left \{ {{\frac{ x^{2} -2x-5}{ x^{2} }=0 \atop {x \neq 0}} \right. => " align="absmiddle" class="latex-formula"> D=4+4*5=24 => x_{1} =1+ \sqrt{6} , x_{2}=1- \sqrt{6}" alt="x^{2} -2x-5=0 => D=4+4*5=24 => x_{1} =1+ \sqrt{6} , x_{2}=1- \sqrt{6}" align="absmiddle" class="latex-formula">